PHYLOGENETIC RELATIONSHIP ANALYSIS OF THREE SPECIEOF ROSA L.,1735 CULTIVATED IN IRAQ BASED ON ITS, matK and trnT-trnL PRIMERS - Jazaa, Liqaa A.; Alwash, Bushra M. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was investigate to demonstrate the phylogenetic relationship among three species of Rosa that are  R. canina L.,1735, R. damascene Mill. and R. centifolia L., cultivated in Iraq by using three primers of ITS, matK and trnL. With regard to the  nuclear ITS sequencing reaction results showed that the identified identities of the investigated samples were R. canina, R. damascena, and R. centifolia the presence of seven nucleic acid variants (g.392G>T, g.439G>A, g.442T>G, g.458C>T, g.477C>T, g.495T>C, and g.496C>T) of  R. canina sample, one nucleic acid variant (g.15A>C) in R. centifolia sample compared with the referring sequences respectively (GenBank acc. no. MT796505.1 and MZ230175.1). Sequencing reaction results for the matK amplicons revealed that the samples under investigation were R. canina, R. damascena, and R. centifolia. This finding suggested the presence of two nucleic acid variations (g.165C>T and g.687G>T) of the R. centifolia sample compared with the referring sequences (GenBank acc. no. MZ261886.1). These amplicons be could quickly and accurately identify the biological diversity of a larger genotype of Rosa sequences.